Clinical relevance of screening checklists for detecting cancer predisposition syndromes in Asian childhood tumours. (December 2018) - Chan, Sock; Chew, Winston; Ishak, Nur; Lim, Weng; Li, Shao-Tzu; Tan, Sheng; Teo, Jing; Shaw, Tarryn; Chang, Kenneth; Chen, Yong; Iyer, Prasad; Tan, Enrica; et al.
Abstract Assessment of cancer predisposition syndromes (CPS) in childhood tumours is challenging to paediatric oncologists due to inconsistent recognizable clinical phenotypes and family histories, especially in cohorts with unknown prevalence of germline mutations. Screening checklists were developed to facilitate CPS detection in paediatric patients; however, their clinical value have yet been validated. Our study aims to assess the utility of clinical screening checklists validated by genetic sequencing in an Asian cohort of childhood tumours. We evaluated 102 patients under age 18 years recruited over a period of 31 months. Patient records were reviewed against two published checklists and germline mutations in 100 cancer-associated genes were profiled through a combination of whole-exome sequencing and multiplex ligation-dependent probe amplification on blood-derived genomic DNA. Pathogenic germline mutations were identified in ten (10%) patients across six known cancer predisposition genes:TP53, DICER1, NF1, FH, SDHD andVHL . Fifty-four (53%) patients screened positive on both checklists, including all ten pathogenic germline carriers.TP53 was most frequently mutated, affecting five children with adrenocortical carcinoma, sarcomas and diffuse astrocytoma. Disparity in prevalence of germline mutations across tumour types suggested variable genetic susceptibility and implied potential contribution of novel susceptibility genes. Only five (50%) children with pathogenic germline mutations had a family history of cancer. We conclude that CPS screening checklists are adequately sensitive to detect at-risk children and are relevant for clinical application. In addition, our study showed that 10% of Asian paediatric solid tumours have a heritable component, consistent with other populations. Cancer: Screening checklists catch Asian children at risk of hereditary tumours Existing checklists designed to screen children for a genetic predisposition to cancer are sensitive enough to detect at-risk individuals in an Asian population. Joanne Ngeow from the National Cancer Centre Singapore and colleagues reviewed the medical records of 102 paediatric patients diagnosed with cancer and profiled for inherited mutations in 100 cancer-associated genes. They crosschecked the records against two published screening instruments used by clinical geneticists to identify patients with a hereditary cancer risk. Although only ten patients harboured known cancer predisposition mutations, the checklists flagged 54 individuals. However, all ten pathogenic gene carriers screened positive on the diagnostic aids. The checklists thus seem to err on the side of over-identification and don't miss many true cases of hereditary cancer in this Asian population.